Driving Behaviour and Public Transport Operation in Lagos Metropolis, Nigeria - Okunubi, S. A.; Jolaoso, G. M. (NIU Journal of Social Sciences, 2025)
During the last decade, Nigeria has been exhibiting rapid increase in human population and vehicular traffic, and increase in road traffic accidents. Regrettably, incessant deviant driving behaviour of public transport drivers is worrisome. This study examines the driving behaviour of commercial drivers and public transport safety in Lagos metropolis. The study employed survey research design. Five motor parks were selected for the investigation, where a total of 68 structured questionnaires were administered to commercial drivers in five (5) selected motor parks in the metropolis. Analysis of Variance and Multiple Regression Analyses were used to explain the research hypotheses at 5% level of significance. The results of the study showed a significant variation (F= 3.175, p= 0.05) among determinants of driving behaviuor of commercial drivers in Lagos metropolis, Nigeria. Age of the Driver (β= .270, t= 8.100) and Type of Vehicle (β= .116, t= 2.208) are driving behaviour of commercial drivers that significantly influence driving experience profile, while License Status (β= .006, t= .175) and Education (β= -.026, t= -.712) have no significant influence on driving experience profile. The result also indicates that driving behaviour of commercial drivers contributed about 33.4% (R 2 = 0.334%) to driving experience profile in the metropolis. It was concluded that improved driver behaviour can be an effective countermeasure to reduce the vulnerability of road users and inhibit crash risks. It is therefore recommended adherence to road traffic safety driving rules and enforcement measures. Keywords: Licensing, Driving, Behaviour, Public Transport, Road Safety